First-Generation Students in Pursuit of the PhD: Comparing Socialization Experiences and Outcomes to Continuing-Generation Peers. (3rd September 2018) - Roksa, Josipa; Feldon, David F.; Maher, Michelle
ABSTRACT: Although first-generation students represent a substantial proportion of doctoral students, few studies have examined their experiences and outcomes. We contribute to this nascent area of inquiry by comparing experiences and outcomes of first-generation and continuing-generation students during the first 3 years of doctoral education. Contrary to expectations, the results based on a national sample of PhD students in biology revealed remarkable similarity in experiences and outcomes between first-generation and continuing-generation students. One notable exception to this overall pattern of similarity was research productivity in the second year. By examining the relationships between students' experiences and outcomes over time, the findings illuminate the unique ways in which socialization experiences are related to specific outcomes and the extent to which those relationships change across years. Thus, this study offers initial insights into the nuanced ways in which students' socialization experiences contribute to various outcomes of doctoral education.